Analysis of the state of internationalisation of small and medium-sized enterprises in Poland - Glinkowska, B. (Економічний вісник Донбасу, 2016)
In the article special attention is focused on the following issues: 1) explanation of the issue of definitional differences of the internationalization process, and presentation of own approach; 2) analyses and presentation of the level of internationalization of Polish companies and their forms; 3) analyses and indication of the level of exports and imports of Polish companies as dominant forms of internationalization in Polish conditions; 4) analyses and identification of the main strategic partners of Polish companies in the area of exports and imports; 5) analyses and presentation of forms of support of state institutions in Poland for companies in their international expansion; 6) analyses and presentation of the level of use by companies of various forms of support; 7) analyses and explanation of reasons for low use of various forms of business support on the way to their internationalization. The author hopes to initiate scientific discussions in this regard, with particular emphasis on Ukraine as "international partner". У статті особливу увагу приділено таким аспектам: 1) висвітленню різних визначень процесу інтернаціоналізації й обґрунтуванню свого власного підходу; 2) аналізу рівня інтернаціоналізації польських компаній та їх форм; 3) дослідженню обсягів експорту та імпорту польських підприємств в якості домінуючих форм інтернаціоналізації; 4) розгляду стратегічних партнерів польських компаній в експортно-імпортних відносинах; 5) аналізу державних форм підтримки в Польщі компаній в здійсненні їх міжнародної експансії; 6) дослідженню використання компаніями різних форм підтримки; 7) розгляду причин недостатнього використання різних форм підтримки бізнесу в здійсненні ним інтернаціоналізації. Автор сподівається, що ця стаття зможе ініціювати наукову дискусію з аналізованої проблеми з акцентом на Україну як особливо важливого партнера Польщі щодо здійснення інтернаціоналізації. В статье особое внимание уделено таким аспектам: 1) освещению различных определений процесса интернационализации и обоснованию своего собственного подхода; 2) анализу уровня интернационализации польских компаний и их форм; 3) исследованию объемов экспорта и импорта польских предприятий в качестве доминирующих форм интернационализации; 4) рассмотрению стратегических партнеров польских компаний в экспортно-импортных отношениях; 5) анализу государственных форм поддержки в Польше компаний в осуществлении их международной экспансии; 6) исследованию использования компаниями различных форм поддержки; 7) рассмотрению причин недостаточного использования различных форм поддержки бизнеса в осуществлении ним интернационализации. Автор надеется, что эта статья сможет инициировать научную дискуссию по анализируемой проблеме с акцентом на Украину как особо важного партнера Польши по осуществлению интернационализации.